2020
DOI: 10.1634/theoncologist.2019-0743
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pretreatment Liver Function Tests Are Associated with Discontinuation of Peptide Receptor Radionuclide Therapy in a U.S.-Based Neuroendocrine Tumor Cohort

Abstract: Background Peptide receptor radionuclide therapy (PRRT) is effective for treating midgut neuroendocrine tumors (NETs); however, incorporation of PRRT into routine practice in the U.S. is not well studied. Herein we analyze the first year of PRRT implementation to determine tolerance of PRRT and factors that increase risk of PRRT discontinuation. Materials and Methods Medical records were reviewed and data were abstracted on all patients with NETs scheduled for PRRT during the first year of PRRT implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Since FDA approval of PRRT, efforts have been targeted at implementation of PRRT within NET clinics across the United States . Results from a 2020 study by our group suggested that PRRT could be successfully administered among a diverse US-based group of patients with NETs, and we found that patients with abnormal liver function tests before PRRT had an increased likelihood of discontinuing PRRT prior to completion of the PRRT treatment course.…”
Section: Introductionmentioning
confidence: 72%
“…Since FDA approval of PRRT, efforts have been targeted at implementation of PRRT within NET clinics across the United States . Results from a 2020 study by our group suggested that PRRT could be successfully administered among a diverse US-based group of patients with NETs, and we found that patients with abnormal liver function tests before PRRT had an increased likelihood of discontinuing PRRT prior to completion of the PRRT treatment course.…”
Section: Introductionmentioning
confidence: 72%
“…Previously, it has been shown that those with less than 25%, 25%-50%, and more than 50% hepatic involvement did not experience significant hepatotoxicity as a result of PRRT (7). A recent study suggested that pretreatment abnormalities of liver chemistries were associated with increased risk of PRRT cancellation, but that study did not address the liver tumor burden and safety of PRRT in patients with extensive liver metastases (14). Several studies have evaluated the estimated absorbed doses of organs and metastatic lesions of patients treated with 177 Lu-DOTATATE (15)(16)(17) and showed wide variation in the mean absorbed dose to tumor lesions, with sample reported average doses of 4.79 6 4.23 Gy/GBq (15) and 3.85 6 1.74 Gy/GBq (18).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hepatic metastasis (mainly those with very high liver burden or impairment [38]) may have an elevated risk of hepatotoxicity after RLT [10], though RLT may continue to be a safe option for these patients [39]. Regardless of tumor burden, baseline hepatic dysfunction may predict premature discontinuation of RLT [40].…”
Section: Risk Of Adverse Events and Laboratory Monitoringmentioning
confidence: 99%